Indoor Environmental Quality and Student Performance in Naturally Ventilated Classrooms - Połednik, Bernard; Guz, Łukasz; Piotrowicz, Adam; Dumała, Sławomira Maria; Badora, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Measurements of indoor air constituent concentrations and thermal parameters were conducted in three naturally ventilated classrooms during the heating season using low-cost sensors. The presence of students significantly affected indoor air composition and microclimatic conditions, leading to elevated CO2 levels and higher concentrations of selected pollutants. During lessons, the acceptability of indoor air quality (ACC) decreased, while the percentage of dissatisfied students (PD), determined based on ACC, increased.
Keywords: classroom; indoor air quality; thermal conditions; indoor environmental quality; student performance